2021
DOI: 10.3390/ijerph18168888
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Energy Poverty and Individual Development: Exploring the Serial Mediating Effects of Learning Behavior and Health Condition

Abstract: Energy poverty has negative impacts on the residents' life from various aspects. A comprehensive understanding of these impacts is the top priority in energy poverty governance. Previous qualitative studies have shown that energy poverty has the potential to negatively impact the individual development of residents through multiple pathways. However, few scholars have explored this issue from a quantitative perspective. To fill the gaps in existing research, this study aims to examine the impact of energy pove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The main dependent variable in this paper is energy poverty at the household level, denoted as . Referring to Zhang et al [ 60 ], Xiao et al [ 61 ], Du et al [ 1 ], and Wang et al [ 62 ], this paper constructs an energy poverty indicator combining two aspects of energy affordability and accessibility, as expressed in equation (1) . Specifically, energy affordability is measured by a 10 % economic threshold.…”
Section: Methodsmentioning
confidence: 99%
“…The main dependent variable in this paper is energy poverty at the household level, denoted as . Referring to Zhang et al [ 60 ], Xiao et al [ 61 ], Du et al [ 1 ], and Wang et al [ 62 ], this paper constructs an energy poverty indicator combining two aspects of energy affordability and accessibility, as expressed in equation (1) . Specifically, energy affordability is measured by a 10 % economic threshold.…”
Section: Methodsmentioning
confidence: 99%
“…Children, women, and the elderly are most susceptible, as are low-income households. Building on this research, Xiao et al [ 46 ] showed that energy poverty has a negative impact on individual development and learning behavior, and that learning behavior and health conditions are correlated with energy poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current research on energy poverty in China falls into three main categories of topics: (1) assessing energy poverty in China [ 57 , 58 ]; (2) exploring the factors [ 59 , 60 , 61 ] influencing energy poverty from macro and micro perspectives; and (3) analyzing the impact of energy poverty on income [ 62 ], health [ 63 , 64 ], personal development [ 65 ], child well-being [ 66 ] and psychological status [ 67 , 68 ] from a household perspective. However, only a small number of studies have discussed the link between buildings and energy poverty [ 24 , 25 , 59 ].…”
Section: Literature Reviewmentioning
confidence: 99%